First Movers Advantages - Montgomery, David B. (Institutional Knowledge at Singapore Management University, 1988)
A study examined theoretical and empirical literature to gain insight into the advantages and disadvantages that accrue to first-mover, or pioneering, firms. There are 3 primary advantages to being a first-mover firm. The first, technological leadership, results from advantages derived from the learning or experience curve and success in patent or research and development races. The 2nd advantage occurs when the pioneering firm is able to preempt rivals in the acquisition of scarce assets such as physical resources or other process inputs. The 3rd advantage arises when buyers incur costs when attempting to switch from the first-mover brand to the brand of a late entrant in the market. Disadvantages for first-movers are essentially the advantages enjoyed by late-entrants: 1. the ability to free-ride on first-mover investments, 2. resolution of technological and market uncertainty, 3. technological discontinuities that provide new paths for entry, and 4. types of inertia that make it difficult for the incumbent to adapt to environmental change.